Diversity and seasonality of Scarabaeinae (Coleoptera: Scarabaeidae) in forest fragments in Santa Maria, Rio Grande do Sul, Brazil - PEDRO G. DA SILVA; FERNANDO Z. VAZ-DE-MELLO; ROCCO A. DI MARE (Anais da Academia Brasileira de Ciências, 2013)
Scarabaeinae specimens were collected with the use of pitfall traps baited with human excrement, rotten meat and rotting banana, between May 2009 and April 2010, in three forest fragments in Santa Maria, Rio Grande do Sul, Brazil: ‘Morro do Elefante' (MOEL), ‘Morro do Cerrito' (MOCE) and ‘Campus da Universidade Federal de Santa Maria' (UFSM). A total of 19,699 individuals belonging to 33 species were collected. Canthidium aff. trinodosum Boheman, 1858, Canthon latipes Blanchard, 1845, Dichotomius assifer (Eschscholtz 1822), Eurysternus caribaeus (Herbst 1789), Canthidium sp. and Canthon lividus Blanchard, 1845, were the most abundant species. MOEL showed the greatest richness, MOCE the greatest abundance, while UFSM showed the lowest values of richness and abundance. The greatest similarity (qualitative and quantitative) was found between MOEL and MOCE, while the lowest occurred between MOCE and UFSM. Only 51% of the species were common to all three fragments. The richness and abundance of Scarabaeinae were positively correlated with the air temperature. The richness of the fragment decreased according to the smaller size and the greater degree of disturbance of vegetation structure. Espécimes de Scarabaeinae foram coletados com o uso de armadilhas de queda iscadas com excremento humano, carne apodrecida e banana em decomposição, entre maio de 2009 e abril de 2010, em três fragmentos florestais em Santa Maria, Rio Grande do Sul, Brasil: Morro do Elefante (MOEL), Morro do Cerrito (MOCE) e Campus da Universidade Federal de Santa Maria (UFSM). Um total de 19.699 indivíduos de 33 espécies foi coletado; Canthidium aff. trinodosum Boheman, 1858, Canthon latipes Blanchard, 1845, Dichotomius assifer (Eschscholtz 1822), Eurysternus caribaeus (Herbst 1789), Canthidium sp. e Canthon lividus Blanchard, 1845 foram as espécies mais abundantes. MOEL apresentou a maior riqueza, MOCE a maior abundância, enquanto UFSM teve os menores valores de riqueza e abundância. A maior similaridade (qualitativa e quantitativa) ocorreu entre MOEL e MOCE, enquanto a menor ocorreu entre MOCE e UFSM. Apenas 51% das espécies foram comuns aos três fragmentos. A riqueza e a abundância de Scarabaeinae estiveram positivamente correlacionadas com a temperatura do ar. A riqueza dos fragmentos diminuiu conforme o menor tamanho e maior grau de perturbação da estrutura da vegetação.